1999
DOI: 10.1037/0096-1523.25.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Identifying stimuli of different perceptual categories in mixed blocks of trials: Evidence for cost in switching between computational processes.

Abstract: Responding to stimuli of different perceptual categories is usually faster when the categories are presented isolated from each other, in pure blocks, than when they are presented intermixed, in mixed blocks. According to criterion models, these perceptual mixing costs result from the use of a less conservative response criterion in pure than in mixed blocks. According to alternate processing models, mixing costs result from time-consuming switching in mixed blocks between different computational processes cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 57 publications
4
45
0
Order By: Relevance
“…Rogers and Monsell also found that this switch cost decreased when the interval between one stimulus and the next (the response-to-stimulus interval, or RSI) was increased but that there was an irreducible switch cost that was not removed, no matter how long RSI became. Other researchers have since replicated and extended these findings, using the repeated runs design (e.g., De Jong, 2000;Gilbert & Shallice, 2002;Karayanidis, Coltheart, Michie, & Murphy, 2003;Lien, Schweickert, & Proctor, 2003;Los, 1999;Nieuwenhuis & Monsell, 2002;Sohn & Anderson, 2003;Yeung & Monsell, 2003).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Rogers and Monsell also found that this switch cost decreased when the interval between one stimulus and the next (the response-to-stimulus interval, or RSI) was increased but that there was an irreducible switch cost that was not removed, no matter how long RSI became. Other researchers have since replicated and extended these findings, using the repeated runs design (e.g., De Jong, 2000;Gilbert & Shallice, 2002;Karayanidis, Coltheart, Michie, & Murphy, 2003;Lien, Schweickert, & Proctor, 2003;Los, 1999;Nieuwenhuis & Monsell, 2002;Sohn & Anderson, 2003;Yeung & Monsell, 2003).…”
mentioning
confidence: 85%
“…Some theories use the concept of "task-set inertia" (TSI), which has garnered substantial empirical support (e.g., Allport, Styles, & Hsieh, 1994;Gilbert & Shallice, 2002;Los, 1999;Yeung & Monsell, 2003). Theories including TSI propose that each of the two tasks to be performed has an associated task set, loosely defined as a mental state that must be prepared in order to accomplish that task.…”
Section: The Failure-to-engage Hypothesismentioning
confidence: 99%
“…For example, Mayr (2001) used 8 different stimuli in one experiment in comparison to the 62 stimuli used in the present study. If the number of stimulus repetitions is large, then uncertainty (or interference) to select among currently relevant task sets will be increased and the response criterion is set more conservatively for switching conditions (Los, 1999), so that latencies would increase. The current literature does not indicate whether this would have an impact on task switching performance.…”
Section: Comparison With Other Findingsmentioning
confidence: 99%
“…Thus, general switch costs are derived at a block level of analysis, whereas specific switch costs are computed at the trial level (for a similar distinction, see Mayr, 2001). Other researchers define general switch costs, which they call ''mixing costs,'' as the difference between performance of trial repetitions in switch blocks and performance in single-task blocks (e.g., Los, 1999). Differences between these two approaches are discussed in more detail at the end of Results and Discussion.…”
mentioning
confidence: 99%
“…The basic semantic feature, animacy, was either repeatedly classified (blocked classification mode) or randomly alternated by an additional semantic classification (mixed classification mode). Task mixing has been shown to affect performance in various tasks (for a review see Los, 1996Los, , 1999aLos, , 1999b, and we expected it to slow down the animacy classification.…”
Section: Experimental Paradigmmentioning
confidence: 99%